Rasch model analysis of essay questions to measure literacy and numeracy skills in plant and animal bioprocess topics based on AKM - Wardani, Rianti Tri; Nuraeni, Eni; Diana, Sariwulan (REID (Research and Evaluation in Education), 2025)
Literacy skills in reading and numeracy in Indonesia are classified as low, so the government has made new policies, one of which is the application of questions based on the Minimum Competency Assessment (AKM) in the National Assessment. Observation results from several high schools in Pekanbaru, Riau, have not shown the application of AKM questions to biology learning. This research aimed to produce AKM-based reading and numeracy literacy instruments on high school plant and animal bioprocess materials used in Research and Development (R&D) design, where the subjects were grade XII students at three high schools in Pekanbaru city. Data collection instruments were the test instruments that had been developed. Data were analyzed using Rasch modelling assisted by Winstep software, including Wright map analysis, person capability analysis, item capability analysis, scalogram analysis, and question item analysis. The results show that most students have a logic score below 0.0, meaning that reading and numeracy literacy skills and understanding concepts are still low. Four out of 63 students have inappropriate answer patterns, indicating that students did not work on the questions seriously. Then, the analysis results show 14 fit questions; having a Cronbach alpha value of 0.84 with a very high interpretation, a person reability value of 0.77 with sufficient interpretation, and an item reability value of 0.92 in the very high category; the difficulty level of the question items is in line with the rules of the test instrument development, since there is a spread of difficulty of the question items starting from very difficult, hard, medium, easy, and very easy. Thus, it is concluded that the instrument test can be used to measure reading literacy and numeracy skills based on AKM on plant and animal bioprocess materials.